Argipressin-norepinephrine association in the treatment of septic shock: the use of the polydistrectual resistance index as an assessment of vascular compliance - Barile, Alessio; Mazzotta, Barbara; Izzi, Antonio; Mirabella, Lucia; Cinnella, Gilda; Paternoster, Gianluca; Mincolelli, Giuseppe; Recchia, Andreaserena; Tonti, Maria Pia; Manuali, Aldo; Copetti, Massimiliano; Restivo, Luciano; et al. (Frontiers in Anesthesiology, 2023)
Introduction The hemodynamic management of septic patients involves initial fluid therapy, followed by the use of vasoconstrictors in case of treatment failure. The latest Surviving Sepsis Campaign guidelines suggest the synergistic use of argipressin in addition to norepinephrine when hemodynamic optimization is not achieved with norepinephrine alone. Methods In our single-center retrospective observational study, the primary endpoint is the safety of initial norepinephrine-argipressin association treatment, assessed through a reduction in Resistance Index. Our secondary endpoint includes the efficacy of this combination, measured by an increase in Mean Arterial Pressure and a reduction in Resistance Index as an indicator of organ perfusion. The Resistance Index (RI) is evaluated through Power Doppler ultrasound. RI is crucial for assessing multi-district vascular tone and multiorgan perfusion. Patients were categorized into three groups based on their treatment. In Group 1, we analyzed patients treated with norepinephrine alone in incremental doses; in Group 2, we analyzed patients receiving the initial norepinephrine-argipressin association treatment (norepinephrine 0.05 mcg/kg/min-argipressin 0.03 IU/min); in the third group (Group 3), we analyzed patients given argipressin (0.03 IU/min) after norepinephrine (<0.10–0.25≥ mcg/kg/min) to stabilize their hemodynamics (MAP > 65 mmHg). RI measurements were taken in the Renal Artery (ARE), Radial Artery (AR), Central Retinal Artery (CRA), and Superior Mesenteric Artery (AMS) at four different time points: T0 before vasopressor therapy, T1 at 1 h, T2 at 24 h, and T3 at 48 h after vasopressor infusion. Results A total of 48 patients were divided into three groups: 17 patients in Group 1, 16 in Group 2, and 15 in Group 3. In Group 1, an increase in Mean Arterial Pressure (MAP) was observed, but there was an increase in RIs in the right CRI and left ARE. In Group 2, there was an improvement in MAP and a reduction in RIs in the right/left CRI, left ARE, AMS, and right AR. In Group 3, there was an increase in MAP and a reduction in RIs in the right/left CRI, left ARE, AMS, and right AR. Conclusion Early norepinephrine-argipressin association treatment appears to be a valid strategy for hemodynamic optimization in this patient population.